1981
DOI: 10.1038/hdy.1981.96
|View full text |Cite
|
Sign up to set email alerts
|

Modification of gene suppression in Drosophila melanogaster by sex chromosomes: I. Effect of the Y chromosome on variegation in malpighian tubules of wm4 larvae

Abstract: SUMMARYThe effect of the Y chromosome on white variegation associated with In(1)w"4 has been investigated by comparing the occurrence, proportion and distribution of colourless cells in the Malpighian tubules of XO, XY and XYY larvae cultured at 25°C or 15°C. The results confirmed previous observations that the Y chromosome suppresses variegation, and showed that its loss from the XY complement has a much greater effect on the proportion of colourless cells than its addition. The variegation is markedly more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Some preliminary observations on the eyes of Wm4 flies from a strain used for studies on Malpighian tubules (Hartmann-Goldstein and Koliantz, 1981) confirmed the fine-spot variegation initially reported in m4 (Muller, 1930) but suggested that neither as regards pattern nor gradient could the variegation be allocated unequivocally to either of the types cited above-a conclusion also reached by Becker (1978). Furthermore, the disparate descriptions of wm4 eyes to be found in the literature seem to imply an unusual variability in the expression of the phenotype, although some of the discrepancies may be due to differences between different m4 lines (Schultz, 1943).…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Some preliminary observations on the eyes of Wm4 flies from a strain used for studies on Malpighian tubules (Hartmann-Goldstein and Koliantz, 1981) confirmed the fine-spot variegation initially reported in m4 (Muller, 1930) but suggested that neither as regards pattern nor gradient could the variegation be allocated unequivocally to either of the types cited above-a conclusion also reached by Becker (1978). Furthermore, the disparate descriptions of wm4 eyes to be found in the literature seem to imply an unusual variability in the expression of the phenotype, although some of the discrepancies may be due to differences between different m4 lines (Schultz, 1943).…”
Section: Introductionmentioning
confidence: 56%
“…It has already been pointed out in the previous section and elsewhere (Hartmann-Goldstein and Koliantz, 1981) that Y chromosome constitution is a more potent modifier of m4 position effect than culture temperature. Also of relevance are the asymmetric shape of the eye itself and the observations that sensitivity varies round the edge of the eye and that the most sensitive region is more or less in the middle.…”
Section: Discussior (I) Types Of Variegation Patternsmentioning
confidence: 62%
See 1 more Smart Citation
“…The stocks and breeding programmes used for our phenotypic studies of m4 variegation, more fully described in Hartmann-Goldstein and Koliantz (1981), were again employed. Male larvae with the normal sexchromosome constitution were taken from strain In(1)wm4.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative, albeit less direct, approach is to analyse the phenotype of affected organs and heterochromatisation in the same strain. We recently obtained quantitative information on white-variegation in Malpighian tubules and eyes of males carrying In(1)wm4 (Hartmann-Goldstein and Koliantz, 1981;Koliantz et a!., 1984). The present paper deals with observations on the salivary gland chromosomes of wm4/yY, wm4,/y and wm4/O larvae in relation to some of the questions arising from phenotypic studies.…”
Section: Introductionmentioning
confidence: 99%